OLIY HARBIY TA’LIM MUASSASASI KURSANTLARINING TA’LIM MUVAFFAQIYATINI BELGILAYDIGAN SHAXSIY OMILLAR - Mirzaolim Rahimjonov Hakimjon o‘g‘li (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA’LIMNING INNOVATSION YO’NALISHLARI, 2025)
This article examines the personal factors that affect the educational success of military cadets. These factors include aspects such as the personal qualities, intellectual potential, psychological state, level of motivation, and self-management skills of military cadets. The article examines the impact of personal factors on the educational process based on empirical research, showing their impact on the level of knowledge acquisition, mastery, and future professional success of cadets. It also recommends methods and approaches aimed at developing personal factors. The article serves as a scientific and practical resource for leaders, teachers, and psychologists of military educational institutions to help improve the educational success of cadets.